Longitudinal Assessment of Parkinson’s Motor Symptoms and Dopaminergic Dysfunction Patterns Using DaTSCAN - Amir Hossein Najmi; Armin Ariaei; Mahboobeh Khezri; Masoud Noroozi; Melika Arab Bafrani; Avesta Gheysari; Farideh Sabetghadam; Mehdi Ahmadi; Mohammad Sadeghi; Mahsa Mayeli (Clinical Parkinsonism & Related Disorders)
Introduction: Determining Parkinson’s disease (PD) stage and severity are among the factors affecting treatment strategy. Dopamine transporter scan (DaTSCAN) has high efficiency in the diagnosis of PD, while its role in predicting motor function, dyskinesia, and symptoms severity trajectory remains controversial. This study aimed to evaluate the associations between motor symptoms patterns in PD with DaTscan findings. Methods: A total of 196 patients were included and grouped based on tremor score, postural instability and gait difficulty score, and the presentation of dyskinesia. Multivariate and ordinal logistic regression models were used to investigate the association between two-year follow-up of the PD patients’ motor symptoms assessment scores and DaTSCAN finding patterns. Results: Patients with dyskinesia exhibited significantly lower DaTSCAN uptake across all measured regions, with the most pronounced reductions observed in the right caudate and left putamen (p < 0.001). Additionally, DaTSCAN values were strongly associated with overall disease severity (p < 0.001). A notable positive correlation was found between DaTSCAN uptake and Schwab and England Activities of Daily Living (ADL) scores, whereas significant negative correlations were observed between DaTSCAN measures (including the caudate, putamen, and anterior putamen) and clinical motor scores, such as MDS-UPDRS III, MDS-UPDRS II, and PIGD. In contrast, DaTSCAN parameters did not significantly predict tremor-dominant (TD) scores. Conclusion: Beyond its diagnostic utility, DaTSCAN provides meaningful insights into disease severity and motor dysfunction in PD, with particular relevance to postural instability and gait disturbance.